Identifying Adjective Phrases and Gradable Structure in Newspaper” The Jakarta Post” - Putri, Yuki Priliani (UIN Alauddin Makassar, 2023)
The adjective that can be modified by degree words or degree adverbs is gradable adjectives. Gradable can also happen to adjectives participial, but not all of them. The adjective phrase has three main functions: attributive adjectives (modified before or after nouns), subject complement (complement subject NPs), and object complement (complement of the object of a clause. This paper focuses on identifying adjective phrase structure and its functions, exploring the categories which are modified, and determining the gradable within the adjective phrase. This paper aims to discover phrases, identify the adjective phrase, and analyze it in the tree diagram. It applied qualitative descriptive method to analyze, and documentation technique to collect the data. The data were obtained from the newspaper of ‘The Jakarta Post’ Vol. 37 No. 086 on Saturday, August 10th, 2019. The result found that pre-modifier (degree words and degree adverbs) + Adjective is the most frequent gradable adjective occurred in the texts, and then it is followed by an adjective (head), double adjectives, and pre-modifier (determiners) + adjectives.